2022
DOI: 10.1111/aswp.12273
|View full text |Cite
|
Sign up to set email alerts
|

Child well‐being in the context of family harmony: Parental marital relationship as mediator and parent–child attachment style as moderator

Abstract: Extant research in Western countries have indicated that children's well‐being may be influenced by children's own resilience, parent–child attachment, and parental marital relationship. Yet, there is very little research in Malaysia on how these factors may influence well‐being among children in middle childhood. The aim of this study, therefore, was to explore the relationships among children's self‐efficacy—a resilience factor—and well‐being, parental marital relationship, and parent–child attachment style.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It is also found that children's well‐being may be influenced by children's own resilience, parent–child attachment, and parental marital relationship. Parental harmony was a significant mediator for the relationship between children's self‐efficacy and well‐being; parent–child attachment style was a significant moderator for the relationship between children's self‐efficacy and well‐being (Mohd‐Zaharim & Hashim, 2023). On the other hand, belongingness can play an important role in community well‐being.…”
mentioning
confidence: 99%
“…It is also found that children's well‐being may be influenced by children's own resilience, parent–child attachment, and parental marital relationship. Parental harmony was a significant mediator for the relationship between children's self‐efficacy and well‐being; parent–child attachment style was a significant moderator for the relationship between children's self‐efficacy and well‐being (Mohd‐Zaharim & Hashim, 2023). On the other hand, belongingness can play an important role in community well‐being.…”
mentioning
confidence: 99%